Associations Between Resolvin D1 and Culprit Plaque Morphologies: An Optical Coherence Tomography Study in Patients with ST-Segment Elevation Myocardial Infarction - Chen R; Li J; Sheng Z; Zhou J; Wang Y; Zhao X; Li N; Liu W; Liu C; Zhou P; Chen Y; Yan S; et al. (Dove Medical Press, 2023)
Runzhen Chen,1,2,* Jiannan Li,1,3,* Zhaoxue Sheng,4 Jinying Zhou,1,3 Ying Wang,1 Xiaoxiao Zhao,1,3 Nan Li,1 Weida Liu,5 Chen Liu,1,3 Peng Zhou,1,3 Yi Chen,1,3 Shaodi Yan,2 Li Song,1- 3 Hongbing Yan,2,3 Hanjun Zhao1,3 1Department of Cardiology, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences, Beijing, People's Republic of China; 2Fuwai Hospital, Chinese Academy of Medical Sciences, Shenzhen, People's Republic of China; 3Coronary Heart Disease Center, Fuwai Hospital, Chinese Academy of Medical Sciences, Beijing, People's Republic of China; 4Department of Cardiology, China-Japan Friendship Hospital, Beijing, People's Republic of China; 5Medical Research Center, Peking Union Medical College Hospital, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Hongbing Yan, Fuwai Hospital, Chinese Academy of Medical Sciences, 12 Langshan Road, Nanshan District, Shenzhen, 510000, People's Republic of China, Email hbyanfuwai2018@163.com; hbyanfuwai@aliyun.com Hanjun Zhao, Fuwai Hospital, National Center for Cardiovascular Diseases, Peking Union Medical College and Chinese Academy of Medical Sciences, 167 North Lishi Road, Xicheng District, Beijing, 100037, People's Republic of China, Email 15210020808@163.comBackground: As a specialized pro-resolving lipid mediator, resolvin D1 (RvD1) inhibits atherosclerosis progression in vivo by reducing regional oxidative stress and chronic inflammation. However, it is unclear how RvD1 is involved in human coronary artery disease. This study aims to investigate the association between plasma levels of RvD1 and culprit-plaque characteristics in patients with ST-segment elevation myocardial infarction (STEMI).Methods: A total of 240 STEMI patients undergoing optical coherence tomography (OCT) examination were analyzed. RvD1 levels were measured in patient plasma samples using an enzyme-linked immunosorbent assay. Logistic regression was performed to assess the association between RvD1 levels and various culprit plaque morphologies, and the receiver operating curve was used to search for an optimal cutoff threshold to predict certain pathological features.Results: The median RvD1 level was 129.7 (56.6- 297.8) pg/mL. According to multivariable logistic regression, high RvD1 was associated with plaque rupture (≥ 111.5 pg/mL, odds ratio [OR]: 2.09, 95% confidence interval [CI]: 1.20- 3.66, P = 0.010), healed plaques (≥ 246.4 pg/mL, OR: 2.17, 95% CI: 1.11- 4.24, P = 0.023), and calcification (≥ 293.38 pg/mL, OR: 2.10, 95% CI: 1.21- 3.66, P = 0.008) at culprit lesions.Conclusion: Increased levels of RvD1 were associated with higher instability of coronary atherosclerotic plaques in STEMI patients.Keywords: resolvin D1, specialized pro-resolving lipid mediator, myocardial infarction, optical coherence tomography, atherosclerosis, inflammation